2004
DOI: 10.1186/1741-7015-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy surgical techniques: a systematic review

Abstract: Background: A wide variety of surgical techniques are used to perform vasectomy. The purpose of this systematic review was to assess if any surgical techniques to isolate or occlude the vas are associated with better outcomes in terms of occlusive and contraceptive effectiveness, and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 45 publications
2
57
0
1
Order By: Relevance
“…From the procedure report, this study found that doing no-scalpel vasectomy only took a relatively short amount of time (median 10 minutes; range 7-90 minutes). Other studies found a similar short operative time for no-scalpel vasectomy 6,21,22 . The wide range of operating times in this study might be influenced by operator's experience.…”
Section: Discussionmentioning
confidence: 72%
“…From the procedure report, this study found that doing no-scalpel vasectomy only took a relatively short amount of time (median 10 minutes; range 7-90 minutes). Other studies found a similar short operative time for no-scalpel vasectomy 6,21,22 . The wide range of operating times in this study might be influenced by operator's experience.…”
Section: Discussionmentioning
confidence: 72%
“…La té cnica de la vasectomía usada fue la escisió n y ligadura del conducto deferente con cauterizació n de ambos cabos 8 .…”
Section: Vasectomíaunclassified
“…Based on the review of surgical techniques by Labrecque and associates (Labrecque et al, 2004), no-scalpel vasectomy (NSV) had less surgical complications than other incisional techniques. Other approaches to access vas deferens for vasectomy include pinhole or keyhole, lateral incisions and electro-cautery techniques but they are still investigational in nature.…”
Section: Techniquesmentioning
confidence: 99%